Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Bagian Produksi Penicillin di PT Sanbe Farma Kota Cimahi - Rini Handayani; Yuke Widyawati (POLITEKNIK LP3I, 2026)
This research is motivated by the phenomenon that 70% of employees in the penicillin production department at PT SANBE FARMA, Cimahi City, failed to achieve their target. The main objective of this study is to determine how compensation and work discipline influence employee performance at PT SANBE FARMA, Cimahi City. The research method used in this study is quantitative correlational method. The unit of analysis is 65 employees working at PT SANBE FARMA, Cimahi City. The research instrument uses a questionnaire. The sampling technique uses a sample without probability or saturated sample. The analysis method includes validity test analysis, reliability test, classical assumption test, t test and f test. The results of the study indicate that partially the compensation variable (X1) and work discipline (X2) influence the performance variable (Y). While simultaneously compensation (X1) and work discipline (X2) influence performance (Y) by 58.4% while the remaining 41.6% is the influence of other variables outside this study